Cancer prevention - Senn, Hansjörg; Kapp, Ursula (Springer Berlin Heidelberg, 2007)
"This volume contains the main proceedings of the fourth international conference on ""Cancer Prevention 2006,"" which was held during February 16-18, 2006, in St. Gallen, Switzerland. Written by international experts in the field, the book comprises a comprehensive update on the most recent developments in the upsurging fields of molecular biology and cancer genetics and their interactions with clinical epidemiology and cancer prevention at various levels."
Description based upon print version of record
Keywords: Konferenzschrift -- 2006 -- Sankt Gallen; Konferenzschrift; Prävention; Krebs